Hukou Status, Housing Tenure Choice and Wealth Accumulation in Urban China - Yu Liao; Junfu Zhang (Institute of Labor Economics (IZA), 2020)
In Chinese cities, migrants with rural hukou, compared to residents with local urban hukou, face more uncertainty, have limited access to mortgage finance, and are less eligible for low-cost housing. A simple model demonstrates that for these reasons, rural- to-urban migrants are less likely to own housing units in cities and as a result accumulate less wealth. Our empirical analysis examines a nationally representative household survey from 2013 and uses mother's hukou status as an instrumental variable. We find that household heads with rural hukou are about 20 percentage points less likely to own housing units in cities than comparable household heads with local urban hukou. Consequently, the average household head with a rural hukou owns 310 thousand yuan less housing wealth and 213 thousand yuan less total wealth than comparable household heads with local urban hukou. The average household head with a rural hukou has 286 thousand yuan less in housing capital gains than comparable household heads with local urban hukou. Moreover, we find that these differences are much larger in the first- and second-tier cities, cities with more stringent hukou regulations, and among younger cohorts.
Keywords: R0; R2; H0; 330; hukou; tenure choice; wealth; Chinese economy